Impact of the synergistic effect of pneumonia and air pollutants on newly diagnosed pulmonary tuberculosis in southern Taiwan - Wu, Da-Wei; Cheng, Yu-Cheng; Wang, Chih-Wen; Hung, Chih-Hsing; Chen, Pei-Shih; Chu-Sung Hu, Stephen; Richard Lin, Chun-Hung; Chen, Szu-Chia; Kuo, Chao-Hung (Environmental research, 2022)
An increased incidence of pulmonary tuberculosis (PTB) among patients with pulmonary diseases exposed to air pollution has been reported. To comprehensively investigate the association between pneumonia (PN) and air pollution with PTB through a large-scale follow-up study. We conducted a retrospective study using data from the Kaohsiung Medical University Hospital Research Database and the Taiwan Air Quality Monitoring Database. We included adult patients with PN, PTB and other comorbidities according to ICD-9 codes. Control subjects without PN were matched by age, sex and ten comorbidities to each PN patient at a ratio of 4:1. A total of 82,590 subjects were included. The PTB incidence rate was significantly higher in the PN group (2,391/100,000) than in the control group (1,388/100,000). The crude hazard ratio (HR) of PN-associated PTB incidence decreased with time, and the overall 7 years the HR (95% confidence interval; CI) was 1.74 (1.55-1.96). The overall adjusted HR and 95% CI of PN-related PTB in the multivariate Cox regression analysis was 3.38 (2.98-3.84). In addition, there was a cumulative lag effect of all air pollutants within 30 days of exposure. The peak adjusted HRs for PTB were noted on the 3rd, 8th, 12th and 12th days of PM2.5, O3, SO2 and NO exposure, respectively. The overall peak HRs (95% CI) of PM2.5, O3, SO2 and NO were 1.145 (1.139-1.152), 1.153 (1.145-1.161), 1.909 (1.839-1.982) and 1.312 (1.259-1.367), respectively, and there was a synergistic effect with pneumonia on the risk of PTB. A strong association was found between past episodes of PN and the future risk of PTB. In addition, air pollutants including PM2.5, SO2, O3 and NO, together with previous episodes of PN, had both long-term and short-term impact on the incidence of PTB. [Display omitted] •Past pneumonia (PN) episode is strongly related with later tuberculosis (TB) risk.•The adjusted hazard ratio (aHR) for TB risk after PN episode is 3.38 (2.98–3.84).•PM2.5, O3, SO2 and NO have both long-term and short-term effects on TB risk.•The peak aHR of PM2.5, O3, SO2 and NO noted on occurred 3, 8, 12 and 12 days before TB onset.•PM2.5, SO2, O3, NO and PN have synergistic effects on TB, especially SO2 and PM2.5